Larangan Perkawinan dalam Kondisi Ekonomi Tidak Layak: Analisis Hukum terhadap Perlindungan Anak dan Kelayakan Hidup Keluarga di Indonesia - Yuri Nazar (GLOBAL SCIENTS PUBLISHER, 2026)
Marriage should serve as the foundation for creating a prosperous and harmonious family. However, social realities in Indonesia indicate that many marriages occur without sufficient economic preparedness. This condition often leads to social problems such as domestic conflict, violence, divorce, and the violation of children's rights. This study aims to analyze the impact of inadequate economic conditions on achieving the objectives of marriage as stipulated in Law Number 1 of 1974 in conjunction with Law Number 16 of 2019, as well as to examine the urgency of prohibiting marriage under economically unfit conditions as a means of protecting children’s rights and family welfare. The research employs a normative juridical method with statutory and conceptual approaches. The findings show that economic readiness is a fundamental factor in achieving a prosperous marriage. Therefore, it is necessary to reformulate marriage policies by including economic preparedness as a substantive requirement and strengthening the marriage dispensation mechanism to consider financial conditions and children's welfare. Consequently, such policy reforms are expected to establish a marriage system that is not only legally valid but also just and dignified.